Bone marrow niche-mediated survival of leukemia stem cells in acute myeloid leukemia: Yin and Yang - Zhou, Hong-Sheng (Cancer Biol Med, 2016)
Acute myeloid leukemia (AML) is characterized by the accumulation of circulating immature blasts that exhibit uncontrolled growth, lack the ability to undergo normal differentiation, and have decreased sensitivity to apoptosis. Accumulating evidence shows the bone marrow (BM) niche is critical to the maintenance and retention of hematopoietic stem cells (HSC), including leukemia stem cells (LSC), and an increasing number of studies have demonstrated that crosstalk between LSC and the stromal cells associated with this niche greatly influences leukemia initiation, progression, and response to therapy. Undeniably, stromal cells in the BM niche provide a sanctuary in which LSC can acquire a drug-resistant phenotype and thereby evade chemotherapy-induced death. Yin and Yang, the ancient Chinese philosophical concept, vividly portrays the intricate and dynamic interactions between LSC and the BM niche. In fact, LSC-induced microenvironmental reprogramming contributes significantly to leukemogenesis. Thus, identifying the critical signaling pathways involved in these interactions will contribute to target optimization and combinatorial drug treatment strategies to overcome acquired drug resistance and prevent relapse following therapy. In this review, we describe some of the critical signaling pathways mediating BM niche-LSC interaction, including SDF1/CXCL12, Wnt/β-catenin, VCAM/VLA-4/NF-κB, CD44, and hypoxia as a newly-recognized physical determinant of resistance, and outline therapeutic strategies for overcoming these resistance factors.